The effects of inclusive education policies and administrative circulars on small schools in Namibia - Hamutumua, Teopolina Ndilina-Laudika (Rhodes University, Faculty of Education, Department of Primary and Early Chilhood Education)
The achievement of the right to education for all children in Namibia is fundamentally dependent upon the quality of education provided to these learners irrespective of their social circumstances. Being a sparsely populated region, nearly half of the primary schools in the Kavango West region have fewer than 100 learners; thus, these small schools are regarded as not economically viable. The educational development in rural regions is shaped by limited access to quality, inclusive education and the persistence of low-quality primary education which has resulted in high repetition rates and dropouts. This research is a Critical Discourse Analysis of the education policies and regulations. As a case study, it unpacks Formal Education Circulars on staffing norms and on the closure of small schools, looking at their affordances/constraints on the provision of inclusive quality education for children schooling at small schools in Namibia. Interviews and document analysis were used to gather data. Critical Theory frames the process of ideological critique which, among other things, identifies inequalities and factors that limit human freedom and how such factors can be alleviated. The research asks the question: what are the explicit and implicit underlying realities experienced at one-man schools, which depict the varied situations in which these schools survive? Factors emerging from the study showed that small schools in Namibia are symbols of inequity and the exclusion of educationally marginalised children and their poor communities. Small schools are hardly able to sustain and draw in the resources required to meet the education needs of marginalised communities which fall under the multidimensional poverty index in Namibia. The study found that at the moment there are no deliberate efforts from the Ministry of Education to bring about the necessary changes to small schools, and therefore one-man schools have continued to operate as isolated sections of an inflexible system. It is my contention that deliberate efforts are still needed to improve small schools. Policy decisions that respond to the current challenges faced by one-man schools may be sufficient to bring about noteworthy changes in the operations of one-man schools and these changes could effectively impact the learners learning. The decision to drive change requires a multilayered approach that articulates a clear vision, which is systematically implemented to improve one-man schools in Namibia.
Keywords: Inclusive education-- Namibia Kavango West; Education and state-- Namibia; Small schools-- Namibia Kavango West; Right to education-- Namibia Kavango West; Education Social aspects-- Namibia Kavango West; Business communication